Prevalence estimation and characterization of diseases occurring on ‘Bhut jolokia’ in Assam (Capsicum chinense Jacq.) - A.K. SAIKIA, JURI TALUKDAR* and (Indian Phytopathology, 2016)
Field surveys were carried out in Bhut jolokia growing district of Assam (Sivasagar, Jorhat, Golaghat). Four fungal diseases on Bhut jolokia, anthacnose/Fruit rot caused byColletotrichum capsici, die-back caused by Colletotrichum gloeosporoides, stem rot and wilt caused by Sclerotinia sclerotiorum, collar rot caused by Rhizoctonia solani, leaf spot caused by Corynespora cassicola were identified. Bacterial wilt disease caused by Ralstonia solanacearum was observed on Bhutjolokia at later stages of crop growth. Four different viruses were identified based on symptomatology, transmission and host range studies. These disease were identified as Mosaic caused by Cucumer Mosaic virus (CMV), Potato Virus Y (PVY), Leaf and Stem necrosis disease caused by Tomato Spotted Wilt Virus (TSWV) and Leaf curl disease caused by Chilli Leaf Curl Virus (ChLCV). All the virus diseases (CMV, PVY, TSWV, ChLCV) are easily transmitted by grafting and by sap inoculation.The species of Aphid (Aphis gossypi and Myzuspersicae) transmitted the PVY and CMV virus. Thrips (Scirtothrips dorsalis) was the efficient vector for transmission of TSWV. The whitefly (B. tabaci) transmitted leaf curl disease. The presence of virus (PVY and TSWV) were confirmed trough DAS-ELISA.